Teori Pembelajaran Al Qur'an - Nurul Hidayati (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
This article discusses teaching and learning theories as widely discussed in the academic world, namely behavioristic, cognitivistic and constructivist learning theories, but here the author will analyze its application to learning the Qur'an. Al-Qur'an learning is all teaching and learning processes whose object of study is the Qur'an, such as qiro'ah al-Qur'an, recitation, interpretation, al-Qur'an Hadith, Tahfidh al-Qur'an and the sciences of the Qur'an. another one. However, in this article the author will focus on learning Qiro'ah and Tahfidz al Qur'an, because the learning process requires a slightly different analysis from other materials. Many methods of reading the Qur'an (Qiro'ah al Qur'an) that developed in Indonesia have differences and similarities in the concept of the learning process. Basically these methods adhere to multiple theories, but have a tendency to one theory. Methods with cognitive theory teach reading the Qur'an by showing the characteristics and concepts of letters or readings and giving a few examples for later processing by the brain. While behavioristic theory provides more examples of reading and explains a little about the concept of material, here students are also accustomed to reading repeatedly with the help an example from the teacher. For the method with constructivist theory, students are given the freedom to understand the subject matter themselves and then apply it to the reading, of course, with the guidance of the teacher. For learning Tahfidz al Qur'an, the application of cognitivistic theory is very appropriate to be applied to memorizers who have strong memories or intelligent brains who are able to remember the verses of the Qur'an easily, but habituation or reflection must still exist. However, for memorizing the Qur'an, behavioristic theory is more appropriate, namely with more habituation and support as a stimulus. Memorizing the Qur'an is easier than maintaining it, this is where the application of constructivist theory is needed. Memorizing the Qur'an must be able to rebuild his rote memorization and then relate it to the purpose of the verse, in addition to maintaining memorization, the purpose of the verse can also expand knowledge.